Counseling and Controlling Child Development based on Information Technology at Fajar Harapan Infant and Toddler Orphanage - Yuda Irawan; Refni Wahyuni; Yesica Devis (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The orphanage is the best place for neglected children to get services, education, skills to become quality and useful children for many people. To create all that, it is necessary to improve the quality of the Orphanage. The Fajar Harapan Infant and Toddler Orphanage is currently experiencing several problems, including: Monitoring child growth using only the Manual Towards Health Card (KMS), Lack of knowledge of caregivers about child growth and development, and lack of child health equipment. Based on the existing problems, the following solutions can be given: Designing child development applications; Provide counseling, training and guidance to caregivers related to children's growth and development and nutritional intake, as well as providing orphanage health equipment. From the results of Community Service activities that have been carried out, namely the availability of applications for monitoring web-based growth and development that can be accessed online, making it easier for caregivers to see the growth and development of their foster children and making it easier for administrators to monitor the growth and development of foster children. Availability of health equipment such as scales, height measuring instruments, head circumference measuring instruments, thermometers, mattresses, and first aid kits to support growth and development control. With the existence of growth and development counseling activities, it provides the benefit of increasing caregiver knowledge about child development and increasing caregiver skills in providing nutritional intake and providing stimulation to children so that children's health and growth and development improve better.